2014
DOI: 10.1038/cddis.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine blocks autophagic flux and induces apoptosis via energetic impairment in cancer cells

Abstract: Lysosomes are acidic organelles that have a crucial role in degrading intracellular macromolecules and organelles during the final stage of autophagy. Tetrandrine (Tet), a bisbenzylisoquinoline alkaloid, was reported as an autophagy activator. Here, in contrast with previous studies, we show that Tet is a potent lysosomal deacidification agent and is able to block autophagic flux in the degradation stage. Single-agent Tet induces significant apoptosis both in vitro and in xenograft models. In the presence of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…As alternative transcripts of autophagy related 5 (ATG5) lack one or two exons in DU145 cells, and this causes the autophagy pathway to be genetically impaired (12). By contrast, DU145 cells exhibited the highest sensitivity to Tet in all of the 11 cancer cell lines that were previously tested by the authors of the present study (1), implying that impairment in autophagy may increase Tet-induced cell death. In order to investigate the role of autophagy on Tet-induced cell death in DU145 cells, the ultrastructural changes following Tet treatment were observed by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…As alternative transcripts of autophagy related 5 (ATG5) lack one or two exons in DU145 cells, and this causes the autophagy pathway to be genetically impaired (12). By contrast, DU145 cells exhibited the highest sensitivity to Tet in all of the 11 cancer cell lines that were previously tested by the authors of the present study (1), implying that impairment in autophagy may increase Tet-induced cell death. In order to investigate the role of autophagy on Tet-induced cell death in DU145 cells, the ultrastructural changes following Tet treatment were observed by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 60%
“…Previously, the present authors have demonstrated that Tet induces cell death in 11 cancer cell lines (1). Tet directly neutralizes the lysosomal acidity, blocks the autophagic flux in the degradation step and causes energetic impairment, which eventually results in cell death (1). By contrast, Tet also acts as an autophagy agonist by inducing the synthesis of reactive oxygen species (3,4,(9)(10)(11), indicating that Tet may function as a multi-target drug to regulate autophagy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations